How Do Payday Loans Affect Borrowers? Evidence from the U.K. Market - Gathergood, John; Guttman-Kenney, Benedict; Hunt, Stefan (Review of Financial Studies, 2018)
Payday loans are controversial high cost, short-term lending products, banned in many US states. But debates surrounding their benefits to consumers continue. We analyse the effects of payday loans on consumers using a unique dataset including 99% of loans approved in the UK over a two-year period matched to credit files. Using a Regression Discontinuity research design, our results show payday loans provide short-lived liquidity gains and encourage consumers to take on additional credit. However, in the following months, payday loans cause persistent increases in defaults and cause consumers to exceed their bank overdraft limits.